Application of Dental Lasers in the Field of Endodontics: A Review of Literature - Ghods, Kimia; Asnaashari, Ehsan; Dehmoobed, Andia; Motaharitabari, Seyedehelina; Tofighirad, Nazanin (Iranian Endodontic Journal, 2025)
The present study aims to provide readers with the influence of various types of dental lasers in endodontics, along with their advantages and disadvantages. A complete query was carried out on PubMed, Google Scholar, Embase, and Scopus databases, and the studies published during 2015-2024 were collected using the keywords "Laser," "Endodontics," "Disinfection," "Vital Pulp therapy," and "Regenerative Endodontic Treatment." After applying appropriate inclusion and exclusion criteria, 86 relevant articles focused on the application of dental lasers in endodontics were selected and evaluated. Based on the evaluated studies, probably the most significant advancement of dental lasers is in optimizing the treatment outcome of root canal therapy via enhanced disinfection of root canals. Moreover, various research has shown that dental lasers can also aid in diagnosing vitality of pulp, vital pulp therapy, apiectomy, regenerative treatments, pain management treatment after root canal therapy, access cavity preparation, sterilization and irrigation of root canals, treatment of periapical lesions, removing excess materials and broken instruments in canals, and prompting the healing process after root canal therapy. As evidenced by the obtained results, diode and erbium lasers have the most applications in endodontics with the lowest side effects. Nonetheless, all dental lasers face multiple limitations, including producing noticeable thermal changes and smoke and damaging surrounding structures at the emission site, which question their safe usage in clinical practice. Therefore, dental lasers’ newest advancements in dental procedures require further scientific work in the future.